PENGARUH PENAMBAHAN ABU VULKANIK GUNUNG KELUD TERHADAP KUAT TEKAN BETON - Pramudiyanto, Sadham Panjang Yuswanto (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT This study aims to determine the chemical content Volcanic Ash Kelud and determine the effect of volcanic ash that has burned at a temperature of 600ºC for concrete compressive strength. Testing will be done on the physical properties and chemical composition of the Volcanic Ash content Kelud using Atomic Absorption Spectrometry (AAS) and Gravimetry include the content of Al2O3, Fe2O3, SiO2, H2O and LO1. This test refers to ASTM 618-03 and SNI 15-0302-2004. Further testing concrete compressive strength with three cylindrical concrete specimen with a diameter of 15 cm and a height of 30 cm to 28 days on each variant. The addition of volcanic ash Kelud varied with dose of 0%, 5%, 10%, 15% and 20% of the weight of cement needed. Data were analyzed with descriptive-quantitative method to determine the feasibility of volcanic ash in concrete production based on the requirements of new chemical elements Pozolan nature. The results showed that of the test sample composition chemical constituents Volcanic Ash Kelud from Pringwulung village, Depok, Sleman qualify as natural Pozolan. The greater the increase percentage of volcanic ash on the weight of the cement, the compressive strength of concrete produced increasingly large, the compressive strength of concrete against any variation on the addition of volcanic ash Kelud 0%, 5%, 10%, 15% and 20% obtained compressive strength average amounted to 34.295 Mpa, 36.731 MPa, 41.881 MPa, 42.767 MPa and 46.947 MPa. Where the maximum compressive strength of the concrete obtained with the addition of volcanic ash of 20% and a minimum compressive strength of the concrete obtained with the addition of volcanic ash at 0% (No Addition). Keywords: Chemical Ingredients, Concrete Compressive Strength, Volcanic Ash Kelud